Caracterização do mecanismo de controle do pH no tubo digestivo de Lutzomyia longipalpis (Lutz e Neiva, 1912) (Diptera: Psychodidae) e sua importância no desenvolvimento de Leishmania Ross, 1903 - Vania Cristina dos Santos (2010)
The midgut pH control is a key step during Lutzomyia longipalpis digestion process. Phlebotomines have to change from a favorable carbohydrate digestion (luminal pH = 6) to blood digestion (luminal pH~8). Until blood ingestion, the acidic pH in the midgut is rigorouslymaintained closely to pH 6 by an efficient mechanism. Apparently, alkalization in the abdominal midgut of L. longipalpis can occur due to CO2 volatilization from blood and by a second unknown mechanism. The first objective of our study was to characterize the primary stimulus, responsible for changing the pH from 6 to 8. Our data showed that any ingested protein could induce alkalization. At the concentration found in the blood, amino acids were ineffective to do that, while higher concentrations did. Midgut extracts were able to slightly alkalize the midgut lumen when applied upon dissected intestines. Serotonin did not promote alkalization of dissected intestines. The carbonic anhydrase enzyme (CA) seems to be involved in the alkalization of the midgut since acetazolamide (a CA inhibitor) when ingested with proteins interfered in this process. A general model of alkalization control was provided. Usingion sensible microelectrodes, we found that potassium (K+) concentration in the abdominal midgut content increased during the blood digestion. On the other hand, sodium (Na+) concentration was slightly reduced 26h after blood ingestion. These results indicated thatalkalization in the abdominal midgut during blood digestion can be related to sodium/potassium transport between lumen and enterocytes. To determine the importance of the intestinal pH in the Leishmania infantum development inside L. longipalpis, infected phlebotomines wereexamined. In these insects, pH inside the midgut lumen was acidified more rapidly (pH ~ 7.0) than in uninfected ones (pH ~ 7.5). These data suggested that this acidification may be responsible for a digestion process delay in the infected sandflies.